1998
DOI: 10.1007/s002709900292
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of J-Tip guidewires by venatech and stainless-steel greenfield vena cava filters during central venous catheter placement: Percutaneous management in four patients

Abstract: We present four patients in whom bedside placement of a central venous catheter was complicated by entrapment of a J-tip guidewire by a previously placed vena cava (VC) filter. Two Venatech filters were fragmented and displaced into the superior VC or brachiocephalic vein during attempted withdrawal of the entrapped wire. Two stainless-steel Greenfield filters remained in place and intact. Fluoroscopically guided extraction of both wires entrapped by Greenfield filters was successfully performed in the angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 10 publications
0
40
0
Order By: Relevance
“…38,39 Entrapment was seen only with the original Vena-Tech filter (B. Braun, Evanston, IL), the 12-F stainless steel over the wire Greenfield filter, and the Trapease filter (Cordis Endovascular/Johnson and Johnson, Warren, NJ). 38,39 Percutaneous disengagement and retrieval of the entrapped guide wire using advanced interventional radiology techniques has been reported 34,37,40 and should be the first line of treatment attempted.…”
Section: Discussionmentioning
confidence: 98%
“…38,39 Entrapment was seen only with the original Vena-Tech filter (B. Braun, Evanston, IL), the 12-F stainless steel over the wire Greenfield filter, and the Trapease filter (Cordis Endovascular/Johnson and Johnson, Warren, NJ). 38,39 Percutaneous disengagement and retrieval of the entrapped guide wire using advanced interventional radiology techniques has been reported 34,37,40 and should be the first line of treatment attempted.…”
Section: Discussionmentioning
confidence: 98%
“…There is potential for spontaneous migration of IVC filters [2] and for dislodgment of a filter during catheter manipulations [3]. Furthermore, J-tipped guidewires may become entrapped in filters [4]. In vitro work has shown that straight guidewires do not become entrapped in filters [5].…”
Section: Discussionmentioning
confidence: 98%
“…30 Similarly, the risk increases when longer guide wires are introduced. 2 Although a femoral vein approach places the CVC insertion site in close proximity to an IVC filter, to our knowledge, there have been no reports in the literature of entrapment from a femoral approach.…”
Section: Introductionmentioning
confidence: 95%
“…8. Other techniques: a catheter-directed microforceps may be used to grasp the entrapped guide wire, but this device can cause significant vessel wall trauma if not used properly 2,21. …”
mentioning
confidence: 99%